THE INFLUENCE OF WORK-LIFE BALANCE AND OCCUPATIONAL HEALTH SAFETY (K3) ON EMPLOYEE JOB SATISFACTION - FAHIRA, JIHAN (Talenta Publisher, 2024)
Skilled, qualified, and productive employees play an important role in the performance part of the company. This can be realized with a good work-life balance as well as good health safety. This study aims to analyze the effect of work-life balance and occupational health safety partially on employee satisfaction at PT Indonesia Comnets Plus Medan. This study used a quantitative method involving 58 employees of PT Indonesia Comnets Plus Medan as the research sample. The sampling technique for this study was non-probability sampling and purposive sampling. The data collection used was a questionnaire using a Likert scale. The data analysis technique uses the validity-reliability instrument test, the classical assumption test and the hypothesis test using multiple linear regression analysis using SPSS. The results of this study indicate that work-life balance has no significant effect on employee satisfaction at PT Indonesia Comnets Plus Medan. Meanwhile, occupational health safety has a significant effect on the performance of employees of PT Indonesia Comnets Plus Medan. Simultaneously work-life balance and occupational health safety affect employee satisfaction at PT Indonesia Comnets Plus Medan and are able to influence employee satisfaction by 55%, the remaining 45% is explained by variables or other factors.